Trichia scabra - Krivomaz, Т. І.; Michaud, A.; Minter, D. W. (CABI, 2012)
Diagnostic features. The combination of bright orange-yellow, densely packed sessile sporangia on a brown honeycomb hypothallus, a capillitium with rough elaters and spiny spirals, and delicately reticulate spores is diagnostic for this species.
Keywords: myxomycetes; міксоміцети; Trichia scabra